Peran Pengasuh dalam Membina Perilaku Sosial Anak pada Panti Asuhan Annur Pasanehan - Dini Rahayu; Elviana Elviana; Elisa Desfira (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
An orphanage is an institution that is known by the community to shape the development of children who do not have a family or who do not live with a family and provide social welfare services to orphans by carrying out sponsorship and reducing child neglect, providing substitute parent/guardian services for children. in meeting the physical, mental, and social needs of foster children. This study aims to describe the role of caregivers in fostering social behavior of children at the Annur orphanage in Pasanehan City. The research method used is a descriptive approach with qualitative data analysis. Data collection through observation and interviews. The results of this study indicate that the caretaker of the orphanage has been considered as a family for every orphan where the caretaker of the orphanage has a function as a place to fulfill affection, physical education, and provide a view of life for children as well as a place to hide the values and norms that apply in society.